2019
DOI: 10.1155/2019/8947204
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Mortality in Patients Undergoing Transcatheter Aortic Valve Replacement for Stenotic Bicuspid versus Tricuspid Aortic Valves: A Meta-Analysis and Meta-Regression

Abstract: Objective. To assess 1-year mortality after transcatheter aortic valve replacement (TAVR) in patients with bicuspid aortic stenosis (AS). Background. Clinical trials have proven the beneficial effect of TAVR on mortality in patients with tricuspid AS. Individuals with bicuspid AS were excluded from these trials. Methods. A meta-analysis using literature search from the Cochrane, PubMed, ClinicalTrials, SCOPUS, and EMBASE databases was conducted to determine the effect of TAVR on 1-year mortality in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
2
4
0
1
Order By: Relevance
“…This systematic review found low rates of procedural and clinical outcomes. Device success rate (87.5%) reported in this study is comparable with previously published systematic reviews, which range from 85.8% to 95.2% (46)(47)(48)(49). Post-procedural mean aortic gradient (11.2 mmHg) was also comparable with previously published gradients, which range from 6.0 to 16.0 mmHg (49,50).…”
Section: Discussionsupporting
confidence: 90%
“…This systematic review found low rates of procedural and clinical outcomes. Device success rate (87.5%) reported in this study is comparable with previously published systematic reviews, which range from 85.8% to 95.2% (46)(47)(48)(49). Post-procedural mean aortic gradient (11.2 mmHg) was also comparable with previously published gradients, which range from 6.0 to 16.0 mmHg (49,50).…”
Section: Discussionsupporting
confidence: 90%
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… References 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 …”
Section: Supporting Informationunclassified
“…A recent study that evaluated the outcomes of TAVI in 170,959 patients with bicuspid AV stenosis (3.2%) in comparison with tricuspid AV stenosis (96.7%) demonstrated comparable procedural, post-procedural, and 1-year outcomes following TAVI in both groups when current-generation devices were used (10). Better outcomes with the new-generation devices were also demonstrated in a recent meta-analyses (12,27). Hence, TAVI seems to be a viable treatment option for patients with BAV, especially with the use of newer-generation devices and careful pre-procedural evaluation by MSCT.…”
Section: Discussionmentioning
confidence: 89%